2012
DOI: 10.1186/1475-2859-11-5
|View full text |Cite
|
Sign up to set email alerts
|

Casein phosphopeptides drastically increase the secretion of extracellular proteins in Aspergillus awamori. Proteomics studies reveal changes in the secretory pathway

Abstract: BackgroundThe secretion of heterologous animal proteins in filamentous fungi is usually limited by bottlenecks in the vesicle-mediated secretory pathway.ResultsUsing the secretion of bovine chymosin in Aspergillus awamori as a model, we found a drastic increase (40 to 80-fold) in cells grown with casein or casein phosphopeptides (CPPs). CPPs are rich in phosphoserine, but phosphoserine itself did not increase the secretion of chymosin. The stimulatory effect is reduced about 50% using partially dephosphorylate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 61 publications
0
14
0
1
Order By: Relevance
“…Supplementation of 0.5% casein enhanced the total cellulase activity by 1.5-fold, while sorbose and cheese whey were found to be detrimental for cellulase and xylanase production (Additional file 1: Table S2). Recently, Kosalkova et al (2012) reported that casein or its biopolymers significantly increased the secretion of extracellular proteins up to 40-to 80-fold in A. awamori. Similarly Kawamori et al (1986) also tested l-sorbose for induction and production of CMCases in T. reesi, where avicel and glucose supplemented with 0.3% sorbose enhanced the CMCase activity by twofold.…”
Section: Effect Of Additives On Cellulases Productionmentioning
confidence: 99%
“…Supplementation of 0.5% casein enhanced the total cellulase activity by 1.5-fold, while sorbose and cheese whey were found to be detrimental for cellulase and xylanase production (Additional file 1: Table S2). Recently, Kosalkova et al (2012) reported that casein or its biopolymers significantly increased the secretion of extracellular proteins up to 40-to 80-fold in A. awamori. Similarly Kawamori et al (1986) also tested l-sorbose for induction and production of CMCases in T. reesi, where avicel and glucose supplemented with 0.3% sorbose enhanced the CMCase activity by twofold.…”
Section: Effect Of Additives On Cellulases Productionmentioning
confidence: 99%
“…Finally, the functional proteomics that provides information about protein functions through the identification of interacting protein partners. Expression proteomics analyses have been carried out in penicillin-producer strains to compare between different them or between different culture conditions [ 64 , 65 , 83 , 87 , 88 , 89 , 90 ]. However, structural proteomics have been used to achieve reference maps of different sub-proteomes (e.g.…”
Section: Proteomicsmentioning
confidence: 99%
“…The addition of calcium salts in the culture medium has a positive effect in penicillin production and it also plays an important role in the growth of P. chrysogenum, whereas casein phosphopeptides are able to chelate Ca 2+ increasing the proteins secretion in Aspergillus strains [ 88 , 122 , 123 ]. The combination of both additives (Ca 2+ and casein phosphopeptides) increased 10–12-fold penicillin production in P. chrysogenum as described Domínguez-Santos and co-workers in 2017 [ 89 ].…”
Section: Proteomicsmentioning
confidence: 99%
“…Fungi are efficient producers of enzymes with biotechnological potential and have advantages, such as production in large amounts, rapid growth and the ability to secrete functional proteins with correct folding and post-translational modifications [6].The genus Aspergillus is a great source for commercial enzymes, and is known for its ability to secrete a high level of enzymes into the environment [7,8]. Aspergillus section Flavi comprise 22 species known as Aspergillus flavus, A. oryzae, A. sojae, A. tamarii, A. parasiticus and recently two new species were identified: A. pseudocaelatus sp.…”
Section: Introductionmentioning
confidence: 99%